“Investigating the Effectiveness of Immersive VR Technologies in Enhancing Learning Outcomes and Engagement”. - Prof (Dr) Neeta Gupta; Dr Vandana Gaur; Dr. Anil Bhatt; Mr. Swapnil Gaur; Ms. Shaina Parveez (Kurdish Studies, 2022)
“Virtual Reality (VR)” technology has emerged as a revolutionary instrument in education, providing immersive encounters with the potential to improve student engagement and academic results. This study aims to systematically evaluate the effectiveness of immersive VR experiences in educational settings and identify factors influencing their success. The objectives include evaluating the impact of VR on learning outcomes, assessing engagement levels compared to traditional methods, identifying influential factors, exploring challenges, and providing evidence-based recommendations. Through a comprehensive review of existing research, this study examines the impact of immersive VR experiences on knowledge acquisition, retention, and transfer of learning. Additionally, it investigates engagement and motivation levels elicited by VR compared to traditional methods, shedding light on the immersive nature of VR environments and its effect on learner engagement. The study also identifies factors influencing the effectiveness of immersive VR technologies, including the design of VR experiences, learner characteristics, and instructional strategies. Furthermore, potential challenges and limitations associated with VR integration into educational contexts, such as technical constraints and ethical concerns, are explored.